An economic assessment of the impacts of the MOSE barriers on Venice port activities - Lucia Vergano; Georg Umgiesser; Paulo A. L. D. Nunes (Fondazione Eni Enrico Mattei (FEEM), 2010)
Due to its hydro-geological features, the lagoon of Venice is especially vulnerable to climate change. In particular, it is strongly affected by gradual global warming that brings about the so-called 'acqua alta' (high water) phenomenon with greater frequency and intensity. In order to protect the city of Venice from the more and more frequent phenomenon of flooding, some protective measures have been adopted. Among them, the system of mobile barriers commonly known as MOSE: however, by separating the lagoon from the Adriatic Sea, it interferes with ship traffic and has negative impacts on port activities. Against this background, the aim of the present work is to provide an estimate of the direct costs of ship traffic interruption due to the functioning of the MOSE, i.e. the additional costs resulting from longer waiting time for ships passing through the Venice lagoon. The estimate uses inputs from the application of a specific hydrodynamic model and the elaboration of ship traffic data during the period 2000-2002. Results indicate that the additional costs would range between 347,943 and 1,288,067 exteuro/year, depending on the hypothesis assumed.
Keywords: Q51; Q54; 330; Climate Change; 'Acqua Alta'; MOSE; Ship Traffic; Direct Costs; Hafen; Hafenwirtschaft; Küstenschutz; Makroökonomischer Einfluss; Venedig